Relationship between Fibroblast Growth Factor-23 and Mineral Metabolism in Chronic Kidney Disease. (26th December 2010) - Nitta, Kosaku
Abstract : Fibroblast growth factor- (FGF-)23 is a recently discovered regulator of calcium-phosphate metabolism. FGF-23 appears to decrease in synthesis and accelerated degradation of 1, 25(OH)2 D. Together with its cofactor Klotho, FGF-23 maintains serum phosphate levels within the normal range by increasing renal phosphate excretion. In chronic kidney disease (CKD), FGF-23 levels rise in parallel with the decline in renal function long before a significant increase in serum phosphate concentration occurs. Both Klotho and FGF-23, linked by a receptor mechanism, affect vitamin D synthesis and parathyroid hormone (PTH) secretion. Previous studies have shown a close association between reduced FGF-23 or Klotho activities and vascular calcification. The possible association of FGF-23 and left ventricular hypertrophy or vascular dysfunction has been proposed. Finally, prospective studies have shown that high serum FGF-23 concentrations predict more rapid disease progression in CKD patients who were not on dialysis and increased mortality in patients on maintenance hemodialysis. FGF-23 may therefore prove to be an important therapeutic target for the management of CKD.